PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN INTERAKTIF MATERI RAGAM BENTANG ALAM PADA MATA PELAJARAN IPAS UNTUK SISWA KELAS III SD NEGERI 060853: Penelitian Pengembangan - Seh Ulina Br Ginting; Natalia Silalahi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to develop interactive educational video media for the Natural and Social Sciences (IPAS) subject, focusing on the diversity of Indonesia’s landscapes, for third-grade students at SD Negeri 060853, as well as to assess the feasibility and practicality of the developed media. This study employed the Research and Development (R&D) method using the ADDIE development model, which encompasses the Analysis, Design, Development, Implementation, and Evaluation stages. Data collection techniques included observation, interviews, questionnaires, and documentation. The results of the study indicate that the interactive educational video received an expert media validation rate of 84% (categorized as highly valid), an expert content validation rate of 90% (categorized as highly valid), and an expert practitioner validation rate of 96% (categorized as highly valid). Questionnaire results showed a teacher response rate of 96% and a student response rate of 86%, both categorized as highly practical. Based on these results, the interactive educational video is deemed suitable and practical for use in IPAS instruction on the topic of Indonesia’s diverse landscapes in third-grade elementary school.